Escala de silhuetas e imagem corporal de adolescentes: revisão sistemática, meta-análise e fatores associados no estudo Saúde em Beagá - Marcela Guimaraes Cortes (2012)
Background: There has been an increasingly number of studies measuring body image, and it has become a multidimensional construct with many available instruments. As such, it is important to be aware of methodological concerns for using such devices more effectively, especially when dealing with adolescents. Aim: To identify and summarize studies that measure adolescents body satisfaction,focusing on the use of silhouette scales as a method of evaluation (review article); To evaluate body satisfaction and its associated factors among adolescents aged 11-17 years old from a large urban center of a developing country (original article). Methods: First article refers to a systematic review regarding adolescents body satisfaction, in which we analyzed studies methodologies and performed a metaanalysisof body satisfaction prevalence. Second one refers to data from 1007adolescents, who completed a questionnaire on a household survey called Saúde em Beagá, conducted by the Observatory for Urban Health in 2008-2009. We investigated association between body satisfaction and individual and sociocultural factors, performing multivariate statistical analyses. Results: We found a great heterogeneity between studies, having the comparison between them been jeopardized by the absence of relevant information. On the second article, we observed the influence of individual and sociocultural on body satisfaction, for both genders. Conclusion: New studies need to be performed, especially aiming at theevaluation of the methodology as well as body-satisfaction related factors. Moreover, here is a need for interventions that focus on emotional development and well-being of adolescents.